2019
DOI: 10.1111/bjso.12321
|View full text |Cite
|
Sign up to set email alerts
|

Parental competitive victimhood and interethnic discrimination among their children: The mediating role of ethnic socialization and symbolic threat to the in‐group

Abstract: Parental competitive victimhood and interethnic discrimination among their children: The mediating role of ethnic socialization and symbolic threat to the in-group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Although families are important contexts for children’s understanding of racism and xenophobia globally, we identified only three empirical studies outside of the U.S. that focused on the explicit content of family ethnic–racial socialization and interethnic–interracial processes specifically (Štambuk et al, 2020; Taylor & McKeown, 2019; van Bergen et al, 2017). In one of these studies, van Bergen et al (2017) investigated the relation between parent ethnic–racial socialization and intergroup attitudes between ethnic majority Dutch (white, Christian, or atheist) and religious minority Muslim (Turkish and Moroccan) youth aged between 16 and 22 years old in the Netherlands.…”
Section: Limitations To What We Know and Directions For Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although families are important contexts for children’s understanding of racism and xenophobia globally, we identified only three empirical studies outside of the U.S. that focused on the explicit content of family ethnic–racial socialization and interethnic–interracial processes specifically (Štambuk et al, 2020; Taylor & McKeown, 2019; van Bergen et al, 2017). In one of these studies, van Bergen et al (2017) investigated the relation between parent ethnic–racial socialization and intergroup attitudes between ethnic majority Dutch (white, Christian, or atheist) and religious minority Muslim (Turkish and Moroccan) youth aged between 16 and 22 years old in the Netherlands.…”
Section: Limitations To What We Know and Directions For Future Studiesmentioning
confidence: 99%
“…Another study also reported that perceived parental ethnic socialization, measured by frequency of conversations on ethnicity and unfair treatment parents previously experienced, positively mediated the link between parents’ experience of ingroup suffering and adolescents’ (13–18 years old) perceived threats to values and norms of their ethnic ingroup. In turn, adolescents’ perceived threat to their ingroup predicted adolescents’ higher likelihood to behave unfairly against the outgroup and higher perceived ethnic ingroup discrimination among Croat and Serb adolescents in Vukovar, Croatia (Štambuk et al, 2020). Therefore, considering the sociopolitical and historical context explicitly to contextualize family ethnic–racial socialization is necessary.…”
Section: Limitations To What We Know and Directions For Future Studiesmentioning
confidence: 99%
“…Victimhood narrative can be used to sustain in-group cohesion and loyalty, gain solidarity from third parties, and to divert attention from the past wrongdoings of the in-group. Thus, groups are motivated to compete for that status (Noor et al, 2012), which further leads to negative intergroup attitudes, less trust, and less willingness to forgive (Noor et al, 2008), with transgenerational negative effects on intergroup relations (Štambuk et al, 2020). Hornsey et al (2015) argue that direct victims are more willing to extend intergroup forgiveness in comparison to indirect victims (in-group members).…”
Section: Interpersonal and Intergroup Perspectives On Apology And For...mentioning
confidence: 99%
“…It may take considerable time to consolidate peace (Lederach, 1997). A majority of research in conflict settings has focused on understanding how the younger generation maintains intergroup hostilities by displaying negative out-group attitudes (e.g., prejudice, Turner et al, 2013) and behaviors (e.g., discrimination, Štambuk et al, 2020; aggression, Taylor et al, 2016). Less is known, however, about the factors that can promote youth’s constructive contributions to rebuilding society after conflict (Taylor et al, 2020b).…”
mentioning
confidence: 99%